2021
DOI: 10.1002/hep4.1654
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the CLIF‐C AD Score in Patients With Implantation of Transjugular Intrahepatic Portosystemic Shunt

Abstract: Prognostic assessment of patients with liver cirrhosis allocated for implantation of a transjugular intrahepatic portosystemic shunt (TIPS) is a challenging task in clinical practice. The aim of our study was to assess the prognostic value of the CLIF‐C AD (Acute Decompensation) score in patients with TIPS implantation. Transplant‐free survival (TFS) and 3‐month mortality were reviewed in 880 patients who received de novo TIPS implantation for the treatment of cirrhotic portal hypertension. The prognostic valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…found the CLIF-C AD score to be a suitable prognostic tool. 33 4) 84 ( 8) 79 ( 13) 76 ( 15) MOTS 1 7 0 (0) 65 ( 5) 62 ( 7) 58 ( 9) 52 ( 14) Several aspects support the assumption that creatinine may not be an ideal prognostic indicator for patients undergoing TIPS. First, the majority of TIPS candidates are patients with decompensated cirrhosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…found the CLIF-C AD score to be a suitable prognostic tool. 33 4) 84 ( 8) 79 ( 13) 76 ( 15) MOTS 1 7 0 (0) 65 ( 5) 62 ( 7) 58 ( 9) 52 ( 14) Several aspects support the assumption that creatinine may not be an ideal prognostic indicator for patients undergoing TIPS. First, the majority of TIPS candidates are patients with decompensated cirrhosis.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, although previous studies have shown predictive inferiority to MELD, 10,14,32 Child‐Pugh score is still broadly used for the selection of patients to receive TIPS. In a recent study, Sturm et al found the CLIF‐C AD score to be a suitable prognostic tool 33 . One thousand and eighty‐eight cases of TIPS placement were analysed, patients who met the criteria of acute‐on‐chronic liver failure (19%) were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In subgroup analysis, none of the models showed significant differences in predictive effect in patients with viral cirrhosis and patients treated for variceal hemorrhage, consistent with the results of Sturm et al . [6]. In patients with nonviral cirrhosis, the Child-Pugh score was significantly better than the FIPS score in predicting 3-month mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the mortality in hospitals after TIPS is 2.3-16.3%, and the mortality at 3 months is 7.9-27.0% [2,3]. Currently, many models have been used to evaluate the outcome of patients treated with TIPS, such as the Child-Pugh score, the model for end-stage liver disease (MELD) score, MELD-Na score, and Chronic Liver Failure Consortium Acute Decompensation (CLIF-C AD) score [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…But, moreover, it has been shown that patientspecific factors such as sarcopenia and cardiac parameters are important risk factors for a negative outcome after TIPS implantation [46][47][48]. There have also been several clinical liver-specific scores such as the Child-Pugh, model for endstage liver disease (MELD [-sodium]) and the chronic liver failure acute decompensation score (CLIF C-AD score) that have been used to predict prognosis after TIPS implantation [49]. However, only the MELD score has been specifically developed for prediction of 3-months mortality after TIPS implantation and is currently predominantly used for allocation to liver transplantation.…”
Section: Selection Of Patients For Transjugular Intrahepatic Portosys...mentioning
confidence: 99%